ANALISIS PERILAKU PETUGAS KEBERSIHAN DALAM PENGELOLAAN LIMBAH MEDIS PADAT COVID-19 DI RSUD DEPATI HAMZAH KOTA PANGKALPINANG - Gita Fajrianti (JURNAL SMART ANKES, 2022)
Hospital is a health service institution that carries out service activities to the community. Depati Hamzah Hospital Pangkalpinang City in its daily activities generates Covid-19 solid medical waste from handling Covid-19 so that there is a need for good and correct Covid-19 solid medical waste management behavior in hospitals in accordance with the provisions of the Minister of Health of the Republic of Indonesia Number HK.01.07 Year 2020 concerning Guidelines for the Prevention and Control of Corona Virus Disease 2019 (Covid-19) and Standard Operating Procedures (SOP) for the Management of Covid-19 Solid Medical Waste in Hospitals. The purpose of this study was to anayzing the behaviour of janitors in the management of solid medical waste Covid-19 at Depati Hamzah Hospital Pangkalpinang city 2022.This research was conducted using a qualitative approach which was presented in an exploratory descriptive manner by means of in-depth interviews with 6 informants at the Depati Hamzah Hospital, Pangkalpinang City, consisting of 4 main informants and 2 supporting informants (triangulation).The result of this study indicates that the behavior of the cleaning staff in the management of Covid-19 solid medical waste at the Depati Hamzah Hospital, Pangkalpinang City is good because the management has been supported by facilities and infrastructure for managing Covid-19 solid medical waste, and already has a policy set out in the Operational Standards. Procedures (SOPs) that have been socialized as well as supervision activities carried out by related units. While the behaviour is not good because personal protective equipment is not available, lack of awareness of the importance of using personal protective equipment and occupational health and safety in janitors in the management of solid medical waste Covid-19.From the results of this study, it is suggested to the Depati Hamzah Hospital Pangkalpinang City to further improve the behavior of janitors in managing Covid-19 solid medical waste to be more optimal by increasing training and socialization as well as monitoring activities.